Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Indonesia Satu Tujuh Jakarta Selatan - Nadia Putri, Istiqomah; Sunardi, Didi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of motivation on employee performance at PT. Indonesia Satu Tujuh South Jakarta. To determine the effect of work discipline on employee performance at PT. Indonesia Satu Tujuh South Jakarta. To determine the effect of motivation and work discipline on employee performance at PT. Indonesia Satu Tujuh South Jakarta. This type of research is quantitative. The data analysis techniques used in this study are instrument test, classical assumption test, regression test, correlation coefficient test, determination coefficient test and hypothesis testing. The population in this study were employees at PT Indonesia One Seven South Jakarta. as many as 69 employees and the sample used was 69 respondents. The results showed that motivation has a positive and significant effect on employee performance, this is evidenced by the value of t count> t table (2.452> 1.996) and sig value <0.05 (0.000 <0.05) so that H0 is rejected and H1 is accepted, there is a positive and significant influence between motivation on employee performance. Work discipline has a positive and significant effect on employee performance, this is evidenced by the value of t count> t table (9.136> 1.996) and sig value <0.05 (0.000 <0.05) so that H0 is rejected and H2 is accepted, there is a positive and significant influence between work discipline on employee performance. Motivation and work discipline have a positive and significant effect on employee performance, this is evidenced by F count> F table (53.275> 3.14) and sig value <0.05 (0.000 <0.05), there is a positive and significant influence between motivation and work discipline simultaneously on employee performance. The coefficient of determination R Square of 0.583 states that, motivation variables (X1) and work discipline (X2) have a contribution of 58.3% to employee performance (Y) and the remaining 41.7% is influenced by other factors